Bridging Innovation to Prevent Ventilator-Associated Pneumonia: A Descriptive Qualitative Study among Critical Care Nurses - Yulis Setiya Dewi; Arina Qona'ah; Hidayat Arifin; Rifky Octavia Pradipta; Rosita Rosita; Lizy Sonia Benjamin (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Ventilator-Associated Pneumonia (VAP) is still a concern for individuals who are dependent on a ventilator. It is envisaged that the growth of technology-based innovations would lead to the creation of remedies for the prevention of VAP.